Cadmus Henry - Edmonds, Walter Dumaux 1903-1998 (Dodd, Mead, 1949)
A novel based upon the experiences of a young soldier who hoped for combat duty under Gerneral Robert E. Lee but was given desk work and scout duty instead. How he learned the real values of army service and the importance of foot soldiers makes an interesting, realistic story especially appealing to young boys